Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Iphone di Kota Karawang - Faizal Hafiz Aria Huda; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Customers' decisions to buy a product are largely influenced by product quality and brand image. One step in the evaluation process is the purchase decision, which requires customers to organize a tier list of products in their preferred tiers. This step in the evaluation process will arouse their interest in making a purchase. The aim of this research is to understand the influence of product quality and brand image on purchasing decisions. The purposive sampling method was used to select a sample of 96 people, and a questionnaire was used to collect data. For data processing, this research uses PLS (Partial Least Square) and other analysis methods, including descriptive analysis. The consequences of this research show that brand image and product quality influence the choice of purchasing an iPhone cell phone.